Biologically Relevant Lighting: An Industry Perspective - Soler, Robert; Voss, Erica (Frontiers in Neuroscience, 2021)
Innovations in LED lighting technology have led to tremendous adoption rates and vastly improved the metrics by which they are traditionally evaluated – including color quality, longevity, and energy efficiency to name a few. Additionally, scientific insight has broadened with respect to the biological impact of light, specifically our circadian rhythm. The data shows that indoor electric lighting, despite its many attributes, fails to elicit a proper biological response. Light levels are biologically too dim during the day, too bright at night, and with many people spending much of their lives in these environments, it can lead to circadian dysfunction. The lighting industry’s biological solution has been to create bluer days and yellower nights, which caters primarily to the visual system. A better call to action is to provide biologically brighter days and biologically darker nights within the built environment. However, current lighting design practices have specified the comfort and utility of electric light. Brighter intensity during the day can often be uncomfortable or glary, and reduced light intensity at night may compromise visual comfort and safety, both of which will affect user compliance. No single lighting solution will effectively create biologically brighter days and biologically darker nights, but rather a variety of parameters need to be considered. This paper discusses the contributions of spectral power distribution (SPD), hue or color temperature (CCT), spatial distribution, as well as architectural geometry and surface reflectivity, to achieve biologically relevant lighting.